Nichotherapy for stem cells: There goes the neighborhood. (5th November 2012) - Levesque, Jean‐Pierre; Winkler, Ingrid G.; Rasko, John E. J.
Abstract Stem cells and their malignant counterparts require the support of a specific microenvironment or "niche". While various anti‐cancer therapies have been broadly successful, there are growing opportunities to target the environment in which these cells reside to further improve therapeutic efficacy and outcome. This is particularly true when the aim is to target normal or malignant stem cells. The field aiming to target or use the niches that harbor, protect, and support stem cells could be designated as "nichotherapy". In this essay, we provide a few examples of nichotherapies. Some have been employed for decades, such as hematopoietic stem cell mobilization, whereas others are emerging, such as chemosensitization of leukemia stem cells by targeting their niche.